Discovery of near-ultraviolet counterparts to millisecond pulsars in the globular cluster 47 Tucanae - Rivera Sandoval, L. E. (2015)
We report the discovery of the likely white dwarf companions to radiomillisecond pulsars 47 Tuc Q and 47 Tuc S in the globular cluster 47Tucanae. These blue stars were found in near-ultraviolet images from theHubble Space Telescope for which we derived accurate absoluteastrometry, and are located at positions consistent with the radiocoordinates to within 0.016 arcsec (0.2σ). We presentnear-ultraviolet and optical colours for the previously identifiedcompanion to millisecond pulsar 47 Tuc U, and we unambiguously confirmthe tentative prior identifications of the optical counterparts to 47Tuc T and 47 Tuc Y. For the latter, we present its radio-timing solutionfor the first time. We find that all five near-ultraviolet counterpartshave U300 - B390 colours that are consistent withHe white dwarf cooling models for masses ?0.16-0.3M⊙ and cooling ages within ?0.1-6 Gyr. The Hα- R625 colours of 47 Tuc U and 47 Tuc T indicate the presenceof a strong Hα absorption line, as expected for white dwarfs withan H envelope.